A FUNÇÃO SOCIAL DA CRECHE NA VISÃO DE FAMÍLIAS DO MUNICIPIO DE INOCÊNCIA-MS. - Amanda Cassia Pereira Frota Garcia (2024)
ABSTRACT This research is linked to the Graduate Program in Education of the Federal University of Mato Grosso do Sul – UFMS, Três Lagoas-MS Campus, specifically the Research Line: Education, Childhood and Diversity, with the aim of unveiling the understanding of guardians/families about the social function of daycare. The study held at CEINF – Margarida Tomázia de Paula – Vó Nona, the only daycare center in the town of Inocência-MS, is based on the hypothesis that the population seeking daycare in the town is unclear about the real social function of this institution. Therefore, the overall goal of this study is to understand what the population of the town – specifically parents or guardians of the children served by the daycare staff – thinks about its social function. It also has the following specific goals: (a) To get to know the socioeconomic profile of the community served; (b) To get to know the parents’ and/or guardians’ understanding of the work being offered by the daycare center; (c) To check how the parents and/or guardians evaluate the work of the daycare center; and (d) To reflect on possible directions that will enable the community in general to understand the current social function of the daycare center and, consequently, to develop its function in a productive and satisfactory way. The qualitative research began with a search for the regulatory documents of the only daycare center in the town of Inocência-MS. The second stage consisted of semi-structured interviews with parents of different educational levels. The analysis of the data, based on the French content analysis technique, showed that there are different understandings of the social function of daycare centers, with emphasis on the understanding that daycare centers have a welfare function: to look after children while their parents go out to work. There was no mention of daycare as being a child’s right. One can see that there is a need to broaden the understanding that daycare is primarily a right for all children and plays a fundamentally important role in human formation and, specifically, in child development, since it is one of the institutions that plays a significant role in terms of welcoming and educating children, becoming a space for socialization and qualified learning. Keywords: Early childhood education; social function of daycare; caring for and educating.